Loss of Highly Influential Figure in Social Anthropology: A Tribute to Fredrik Barth - Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2017)
No abstract available.Dhaulagiri Journal of Sociology and Anthropology Vol.11, 2017; 184-191